Short-term and long-term relationships between consumer demand and economic indicators in crisis and post-crisis periods in Kazakhstan (Journal of Economic Research & Business Administration, 2025)
This article investigates the dynamics of consumer demand in Kazakhstan during episodes of economic crises and subsequent recovery. The study is motivated by the need to better understand the determinants of household behaviour under conditions of macroeconomic instability. Drawing upon theoretical and empirical literature as well as international experience, the analysis identifies key macroeconomic indicators shaping consumption patterns, including gross domestic product, income levels, employment, inflation, credit activity, and government transfers. Particular attention is paid to the short- and long-term consequences of major economic shocks such as the global financial crisis of 2007–2008, the sanctions crisis of 2015–2016, and the COVID-19 pandemic. The results demonstrate that during crisis periods households tend to increase precautionary savings, reduce consumption, and reallocate expenditures towards essential goods and services, while the recovery of demand in the post-crisis period remains slow despite macroeconomic stabilization. The empirical findings have important implications for the design of anti-crisis, fiscal, and monetary policies aimed at supporting domestic demand and ensuring sustainable economic development in Kazakhstan.Key words: consumer demand, macroeconomic factors, economic crisis, pandemic, savings.